DETERMINASI KETIMPANGAN PENDAPATAN WILAYAH PERKOTAAN DAN PERDESAAN DI INDONESIATAHUN 2019 – 2023 - Rania Yasmin; Syofriza Syofyan (Lembaga Penerbit Fakultas Ekonomi dan Bisnis, 2024)
This study aims to examine the effect of economic growth, foreign investment, and human development index on the income inequality in urban and rural areas in Indonesia. This study uses three independent variables economic growth, foreign investment, and human development index. The dependent variable of interest is the Gini Ratio. This study uses data from the period 2019 to 2023 with the panel data regression method. The results showed that aspects of community welfare, namely Average Per Capita Expenditure and Life Expectancy, had a significant effect according to the hypothesis on Inclusive Economic Growth in Indonesia. The variables that have a statistically significant effect according to the hypothesis is the human development index in rural areas. Meanwhile, the economic growth is not by the proposed hypothesis in urban & rural areas because the rate of economic growth is not received evenly or shows a trickling up effect so that it is only felt by a certain group of people.